Wikileaks and consequences for modern diplomacy – observations by a foreign policy practitioner - Møller, Jørgen Ørstrøm (Politik, 2012)
Wikileaks did not reveal much we did not know about U.S. foreign policy already. e true revelations were – as many had suspected – that some foreign leaders pursue a di erent foreign policy agenda than the of- cial one. Sources providing information to foreign diplomats will be more prudent from now on. e main impact is a new type of diplomacy bypassing leaders to communicate directly with the people – increasing people’s power and highlighting the growing importance of civic society and the social media. e ability to intensively monitor social media also brings a markedly better understanding of the domestic context of foreign countries. Events surrounding the Arab spring bears testament to this.